2019
DOI: 10.1038/s41598-019-56996-6
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes of individual macular retinal layers among Asians

Abstract: We characterized the age-related changes of the intra-retinal layers measured with spectral-domain optical coherence tomography (SD-OCT; Cirrus high-definition OCT [Carl Zeiss Meditec]. The Singapore Epidemiology of Eye Diseases is a population-based, cross-sectional study of Chinese, Malays and Indians living in Singapore. Iowa Reference Algorithms (Iowa Institute for Biomedical Imaging) were used for intra-retinal layer segmentation and mean thickness of 10 intra-retinal layers rescaled with magnification co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 60 publications
3
36
0
Order By: Relevance
“…We documented that full RETINA thickness was significantly thicker in men than in women, which is consistent with many previous research works [ 20 , 21 , 28 , 34 , 39 , 45 ]. Previous studies [ 20 , 21 , 31 , 46 ] have reported that GCL, IPL, INL and ONL thicknesses were significantly thicker in men than in women, which falls in line with our results.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We documented that full RETINA thickness was significantly thicker in men than in women, which is consistent with many previous research works [ 20 , 21 , 28 , 34 , 39 , 45 ]. Previous studies [ 20 , 21 , 31 , 46 ] have reported that GCL, IPL, INL and ONL thicknesses were significantly thicker in men than in women, which falls in line with our results.…”
Section: Discussionsupporting
confidence: 93%
“…Finally, we observed that ONL and RPE thicknesses did not correlate with AXL, as described by Invernizzi et al [ 20 ]. However, other authors [ 45 ] have documented a significantly negative correlation between AXL and ONL and RPE thicknesses in the extrafoveal rings of the ETDRS map, probably because these authors did not exclude high myopic eyes.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Specifically, measurements performed with OCT/OCTA have inherent errors when the scale of retinal image is not corrected for axial length (AL) of each eye. [13][14][15][16][17] Of note, a recent systematic review 17 reported that only 41 of 989 peer-reviewed articles (8%) in PubMed that use quantitative OCTA values used AL to correct the scale of OCTA images. This is particularly problematic in pediatric patients with amblyopia, who may have significant differences in AL between the affected and unaffected eyes (especially those with anisometric amblyopia) and considering the fact that measurement of the FAZ area may deviate up to 51% if AL is not factored into the analysis.…”
mentioning
confidence: 99%